Chokeberry Pomace as a Component Shaping the Content of Bioactive Compounds and Nutritional, Health-Promoting (Anti-Diabetic and Antioxidant) and Sensory Properties of Shortcrust Pastries Sweetened with Sucrose and Erythritol - Ewa Raczkowska; Paulina Nowicka; Aneta Wojdyło; Marzena Styczyńska; Zbigniew Lazar (MDPI AG, 2022)
In this study, an attempt was made to develop shortcrust pastries containing different amounts of chokeberry pomace (0%, 10%, 30%, 50%), modulating their degree of sweetness via the application of sucrose or erythritol. The obtained products were assessed for their nutritional value (energy value, protein, fats, dietary fibre, sugars, minerals). Bioactive compounds, as well as antioxidant and anti-diabetic properties in an in vitro model and sensory attributes, were also analysed. Increasing the proportion of chokeberry pomace in shortcrust pastries improved their nutritional value, especially their energy value (reduction of nearly 30% for shortcrust pastries with 50% pomace sweetened with erythritol), nutritional fibre content (10-fold higher in shortcrust pastries with the highest proportion of pomace) and potassium, calcium, magnesium, and iron content. Chokeberry pomace was also a carrier of 14 bioactive compounds. The most beneficial antioxidant and anti-diabetic effect was shown for shortcrust pastries containing 50% chokeberry pomace. In addition, it was shown that the use of erythritol as a sweetener has a beneficial effect on the perception of sensory attributes. Finally, it was shown that the developed products could be excellent alternatives to traditional shortcrust pastries and, at the same time, be a good way to utilize waste from the fruit industry.